EUROPEAN STANDARDS OF SOCIAL DIALOGUE: CHALLENGES AND PROSPECTS OF IMPLEMENTATION IN UKRAINE - Natalia Hromadska (Публічне управління та регіональний розвиток, 2025)
The article is devoted to the analysis of European standards of social dialogue and consideration of the challenges and prospects of their implementation in Ukraine. Social dialogue is presented as a basic element of the European social model and a key mechanism of democratic governance. Particular attention is paid to the role of social partners, the legal principles of their interaction, as well as the practices enshrined in EU regulations, such as the Treaty on the functioning of the EU, the EU Council Recommendation on strengthening social dialogue in the European Union, Tripartite Declaration for a thriving European social dialogue, and others. The author notes that Ukraine's European integration course necessitates the need to bring national legislation into line with European standards. At the same time, social dialogue acts not only as the basis of the European social system, but also forms the foundation for the effective functioning of the socio-economic system of Ukraine, contributing to achieving consensus between government officials, employers and employees in the field of social and labor relations. A separate part of the study is devoted to the challenges caused by the consequences of full-scale Russian aggression, which emphasize the critical importance of coordinating the actions of social partners. The author also examines in detail the initiatives of the Ukrainian authorities to strengthen social dialogue, including the creation of the Office for supporting legislative adaptation, the adoption of the Law «On collective agreements and contracts», and the active participation of social partners in reforming labor legislation. The article also analyses the Tripartite Declaration for a thriving European social dialogue, which has become an important step towards strengthening cooperation between social partners. The measures proposed in the Declaration demonstrate the European Union's desire to set new standards for social dialogue aimed at ensuring stability, justice and the conditions for the development of a democratic society. The study also covers the mechanisms for the practical implementation of the provisions of this document, justifying its importance for Ukraine, which seeks to integrate into the European community and harmonize its political, social, and economic standards in accordance with European practices. It is emphasized that the effective implementation of European standards of social dialogue is the key to increasing socio-economic stability and sustainable development of Ukraine in the context of its European integration.